Sintered body
Patent Information
- Application Number
- JP2023556378
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-10-28
- Filing Date
- 2022-10-20
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2042-10-20
AI Technical Summary
【0007】 本開示によれば、キュリー点が高く、かつ高周波領域において高い透磁率を示す焼結体を提供できる。
Smart Images

Figure 0007639933000003 
Figure 0007639933000001 
Figure 0007639933000002
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a sintered body, and more particularly to a sintered body containing a spinel-type ferrite oxide. [Background technology]
[0002] There is a demand for electronic devices to be smaller and denser, and in recent years, frequencies used have been increasing. In particular, Mn-Zn ferrite, which is easily magnetized in a slight magnetic field and has low power loss, and Ni-Zn ferrite, which has high resistivity, are used as magnetic materials for power supply transformers used in high frequency ranges. Patent Document 1 shows a Ni-Zn ferrite composition with high initial permeability and resistivity that reduces power loss in high frequency ranges. The Ni-Zn ferrite composition contains, as main components, 47.1 to 49.95 mol % of iron oxide calculated as Fe2O3, 2.3 to 10.0 mol % of copper oxide calculated as CuO, 27.6 to 32.0 mol % of zinc oxide calculated as ZnO, and 0.01 to 2.1 mol % of manganese oxide calculated as Mn2O3, with the remainder being nickel oxide. It is shown to contain, as auxiliary components, 2 to 63 ppm of phosphorus calculated as P, 43 to 4530 ppm of zirconium oxide calculated as ZrO2, and 0.01 to 0.15 parts by weight of molybdenum oxide calculated as MoO3, relative to 100 parts by weight of the main components. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2012-96961 A Summary of the Invention [Problem to be solved by the invention]
[0004] In recent years, there has been a demand for magnetic materials that have a high Curie point (Tc) and exhibit higher magnetic permeability in the high frequency range, for example, 100 kHz or higher. However, it is difficult to achieve such characteristics with the Ni-Zn ferrite composition of Patent Document 1, and further improvements are considered necessary. The present disclosure has been made in view of the above circumstances, and its purpose is to provide a sintered body that has a high Curie point and exhibits high magnetic permeability in the high frequency range. [Means for solving the problem]
[0005] According to one aspect of the present invention, The spinel-type ferrite oxide contains Fe, Ni, Cu, and Zn as main components of metal elements, Further, Zr, Mn, Al, Co and Cr are included. When the molar parts of Zn, Ni, Cu, Zr, Mn, Al, Co, and Cr contained in Fe are a, b, c, d, e, f, g, and h, respectively, when Fe is 100 molar parts, a sintered body is provided in which 100-ab-c+2d+(1 / 2)e, a+b+c+d+e / 2, f, g, and h respectively satisfy the following formulas (1) to (5). 49.0<100-ab-c+2d+(1 / 2)e<50.0 ···(1) 50.2 <a+b+c+d+e / 2<52.7 ···(2) 0.0012≦f≦0.010 (3) 0.0005≦g≦0.0015 (4) 0.0005≦h≦0.004 (5)
[0006] In one embodiment of the present invention, in the sintered body, the d satisfies the following formula (6) and the e satisfies the following formula (7). 0.10≦d≦0.50 (6) 0.055≦e≦0.25 (7) Effect of the Invention
[0007] According to the present disclosure, it is possible to provide a sintered body that has a high Curie point and exhibits high magnetic permeability in the high frequency range. [Brief description of the drawings]
[0008] [Figure 1] This is a backscattered electron image of a cross section of a sintered body observed with a scanning electron microscope - wavelength dispersive X-ray spectroscopy (SEM-WDX) and a micrograph showing Cu distribution. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The sintered body according to the present embodiment contains a spinel-type ferrite oxide whose main components are Fe, Ni, Cu, and Zn, Further, Zr, Mn, Al, Co and Cr are included. When Fe is taken as 100 parts by mole, the molar parts of Zn, Ni, Cu, Zr, Mn, Al, Co, and Cr contained therein are a, b, c, d, e, f, g, and h, respectively. Then, 100-ab-c+2d+(1 / 2)e, a+b+c+d+e / 2, f, g, and h respectively satisfy the following formulas (1) to (5). 49.0<100-ab-c+2d+(1 / 2)e<50.0 ···(1) 50.2 <a+b+c+d+e / 2<52.7 ···(2) 0.0012≦f≦0.010 (3) 0.0005≦g≦0.0015 (4) 0.0005≦h≦0.004 (5)
[0010] The spinel ferrite oxide contained in the sintered body of this embodiment contains Fe, Ni, Cu, and Zn as main components of metal elements. In this specification, "main components" refers to 50 mol% or more. The ratio of Fe, Ni, Cu, and Zn to all metal elements contained in the spinel ferrite oxide may be 50 mol% or more, further 60 mol% or more, and further 70 mol% or more.
[0011] The content of each of the main metal elements is not particularly limited. For example, when the content of each metal element is 100 molar parts of Fe, the molar parts of Zn, Ni, and Cu are a, b, and c, a, b, and c are all greater than 0, and a can be in the range of 23.9 to 34.6. b can be in the range of 6.7 to 27.0. c can be in the range of 0.1 to 10.2.
[0012] The sintered body of this embodiment contains the spinel ferrite oxide. The ratio of the spinel ferrite oxide in the sintered body of this embodiment is preferably 90% by mass or more, more preferably 95% by mass or more. The ratio of the spinel ferrite oxide in the sintered body of this embodiment may be substantially 100% by mass, that is, the sintered body of this embodiment may be formed of the spinel ferrite oxide. The sintered body of this embodiment may contain, as an inevitable impurity, for example, carbon, sulfur, etc. derived from the binder used during production, within a range of, for example, a total of 5% by mass or less, or even a total of 1% by mass or less.
[0013] The sintered body of this embodiment further contains Zr, Mn, Al, Co and Cr. The contents of Fe, Ni, Cu and Zn and these elements, expressed as molar parts contained when Fe is 100 molar parts, a, b, c, d, e, f, g and h satisfy all of the above formulas (1) to (5). These formulas will be explained below.
[0014] In this embodiment, it was found that the total amount (mol%) of Fe2O3, Mn2O3 and (3 / 2)ZrO2 in the sintered body, i.e. [Fe2O3+Mn2O3+(3 / 2)ZrO2] is set within a predetermined range, and the contents of Al, Co and Cr are strictly controlled within the above range, thereby significantly improving the magnetic permeability (μ') in the high frequency range (hereinafter, the realization of high μ' may be referred to as "high μ'"). First, the realization of high μ' in the high frequency range by controlling [Fe2O3+Mn2O3+(3 / 2)ZrO2] will be described.
[0015] [Realization of high μ' in the high frequency range by controlling [Fe2O3+Mn2O3+(3 / 2)ZrO2]] Spinel-type ferrite oxides are expressed as AO·B2O3 (A: divalent ions, B: trivalent ions). When the amount of trivalent ions that compose the oxide is excessive, Fe 3+ Part of the 2+ As a result, the magnetic permeability (μ') in the high frequency region decreases. In addition, in spinel ferrite oxides mainly composed of Fe-Ni-Cu-Zn, Mn can also exist as a trivalent ion. Therefore, in the past, a method for increasing magnetic permeability was to suppress the amount of Fe and Mn that can form trivalent ions to a predetermined amount or less. However, in the present invention, a detailed investigation was conducted into the relationship between the composition of spinel ferrite oxides mainly composed of Fe-Ni-Cu-Zn and charge compensation, and it was found that Zr 4+ They then defined [Fe2O3+Mn2O3+(3 / 2)ZrO2] as an index that includes Zr, and when they applied this index to the design of the component composition, they found that it correlated with μ' in the high frequency range, and were able to reliably increase μ' in the high frequency range.
[0016] In the present invention, the molar parts of Zn, Ni, Cu, Zr, and Mn are a, b, c, d, and e, respectively, when Fe is 100 parts by mol, and [Fe2O3+Mn2O3+(3 / 2)ZrO2] is controlled by [100-ab-c+2d+(1 / 2)e] (hereinafter sometimes referred to as "α value") expressed in terms of the molar parts of each of the above elements. First, a method for converting [Fe2O3+Mn2O3+(3 / 2)ZrO2] to [100-ab-c+2d+(1 / 2)e] expressed in terms of the molar parts of each of the above elements will be described.
[0017] Each of Fe, Ni, Zn, Cu, Mn, and Zr contained in the spinel ferrite oxide of this embodiment is converted to an oxide (Fe2O3, NiO, ZnO, CuO, Mn2O3, ZrO2). When the sum of these is taken as 100 parts by mole, the sintered body of this embodiment can reliably increase μ' in the high frequency range by having the contents of Fe2O3, Mn2O3, and ZrO2 satisfy the following ranges. The reason for setting these ranges will be described in detail later. 49.50<[Fe2O3+Mn2O3+(3 / 2)ZrO2]<50.00 ···(1a)
[0018] The above formula (1a) is divided into the following two formulas (1b) and (1c). 49.50<[Fe2O3+Mn2O3+(3 / 2)ZrO2] ···(1b) [Fe2O3+Mn2O3+(3 / 2)ZrO2]<50.00 ···(1c)
[0019] When Fe is taken as 100 parts by mole, the molar parts contained of Zn, Ni, Cu, Zr, and Mn are taken as a, b, c, d, and e, respectively. Then, the molar percentages of Fe2O3, ZrO2, and Mn2O3 can be expressed by using a, b, c, d, and e as shown in the following formulas (1d), (1e), and (1f), respectively. Fe2O3={50 / (50+a+b+c+d+e / 2)}×100 ···(1d) ZrO2={d / (50+a+b+c+d+e / 2)}×100 ···(1e) Mn2O3={(e / 2) / (50+a+b+c+d+e / 2)}×100 ···(1f)
[0020] By substituting the formulas (1d), (1e), and (1f) into the formula (1b), the following formula (1g) is calculated. 49.50<{(50+(3 / 2)d+e / 2) / (50+a+b+c+d+e / 2)}×100 50+a+b+c+d+e / 2<(50+(3 / 2)d+e / 2)×2.02 50+a+b+c+d+e / 2<101+3.03d+1.01e 49.0<100-ab-c+2.03d+0.51e...(1g) In equation (1g), if 2.03 ≒ 2 and 0.51 ≒ 1 / 2, we obtain equation (1h). 49.0<100-abc-2d+e / 2 (1h)
[0021] By substituting the above formulas (1d), (1e), and (1f) into formula (1c), the following formula (1i) is calculated. {(50+(3 / 2)d+e / 2) / (50+a+b+c+d+e / 2)}×100<50.00 100+3d+e<50.0+a+b+c+d+e / 2 100-ab-c+2d+e / 2<50.0 (1i)
[0022] Combining equation (1h) and equation (1i) gives equation (1), where a, b, c, d, and e are all greater than 0. 49.0<100-ab-c+2d+(1 / 2)e<50.0 ···(1)
[0023] If [100-ab-c+2d+(1 / 2)e], which represents the amount (mol%) of [Fe2O3+Mn2O3+(3 / 2)ZrO2], is too small, the amount of oxygen defects in the spinel ferrite oxide increases. To solve this problem, CuO is easily expelled from the spinel crystal during firing, resulting in more CuO segregation and lowering μ' in the high frequency range. Therefore, by increasing the amount of [Fe2O3+Mn2O3+(3 / 2)ZrO2], the amount of oxygen defects can be reduced and μ' in the high frequency range is improved. From these viewpoints, [100-ab-c+2d+(1 / 2)e] is set to be more than 49.0. [100-ab-c+2d+(1 / 2)e] may be 49.5 or more.
[0024] By increasing the [100-ab-c+2d+(1 / 2)e], it is easy to realize a high μ' in the high frequency region. On the other hand, when the [100-ab-c+2d+(1 / 2)e] is 50 or more, the Fe3+ Part of the 2+ Then, Fe 3+ and Fe 2+ Hopping conduction occurs between the nuclei, which causes relaxation loss, lowering μ' in the high frequency region. Therefore, [100-ab-c+2d+(1 / 2)e] is set to be less than 50.0. [100-ab-c+2d+(1 / 2)e] may be 49.8 or less.
[0025] As shown in the prior art, even when the total amount of Fe2O3 and Mn2O3 is about 50 mol% or less, it is difficult to reliably increase μ' in the high frequency range. According to the present invention, it has been found that by making [Fe2O3+Mn2O3+(3 / 2)ZrO2] less than 50.00 mol%, i.e., satisfying 100-ab-c+2d+(1 / 2)e<50.0, it is possible to reliably suppress the decrease in μ' in the high frequency range due to relaxation loss.
[0026] In addition to the above α value, it is also important to specify the amount of Fe2O3 in order to achieve high μ' in the high frequency range. In the following, the realization of high μ' in the high frequency range by controlling the amount of Fe2O3 will be described.
[0027] [Achieving high μ' in the high frequency range by controlling the amount of Fe2O3] By controlling the amount of Fe2O3 in the sintered body of this embodiment, μ' can be reliably improved in the high frequency range. In the present invention, the amount of Fe2O3 (mol%) is controlled by [a+b+c+d+e / 2] (hereinafter sometimes referred to as "β value") expressed in terms of the molar parts of each element, similar to the α value. First, a method for converting the amount of Fe2O3 to [a+b+c+d+e / 2] expressed in terms of the molar parts of each element will be described.
[0028] When Fe, Ni, Zn, Cu, Mn, and Zr contained in the spinel ferrite oxide of this embodiment are converted into oxides (Fe2O3, NiO, ZnO, CuO, Mn2O3, and ZrO2) and the sum of these is taken as 100 parts by mole, the content of Fe2O3 in the spinel ferrite oxide of this embodiment satisfies the following range, thereby reliably increasing μ' in the high frequency range. 48.67 <Fe2O3<49.91 ···(2a)
[0029] The above formula (2a) is divided into the following formulas (2b) and (2c). 48.67 <Fe2O3···(2b) Fe2O3<49.91 (2c)
[0030] When Fe is taken as 100 parts by mole, if the molar parts contained of Zn, Ni, Cu, Zr, and Mn are a, b, c, d, and e, respectively, Fe2O3 can be expressed as the following formula (2d) using a, b, c, d, and e. Fe2O3=50 / (50+a+b+c+d+e / 2)×100 (2d)
[0031] By substituting the above formula (2d) into formula (2b), the following formula (2e) is calculated. 48.67<{50 / (50+a+b+c+d+e / 2)}×100 50+a+b+c+d+e / 2<5000 / 48.67 a+b+c+d+e / 2<52.7 (2e)
[0032] By substituting the above formula (2d) into formula (2c), the following formula (2f) is calculated. {50 / (50+a+b+c+d+e / 2)}×100<49.91 5000 / 49.91<50+a+b+c+d+e / 2 50.2 <a+b+c+d+e / 2 ···(2f)
[0033] Combining equation (2e) and equation (2f) gives equation (2), where a, b, c, d, and e are all greater than 0. 50.2 <a+b+c+d+e / 2<52.7 (2)
[0034] By making [a+b+c+d+e / 2], which represents the amount of Fe2O3, greater than 50.2 and less than 52.7, it is possible to reliably increase μ' in the high frequency region. [a+b+c+d+e / 2] may be 50.4 or more. [a+b+c+d+e / 2] may be 52.0 or less.
[0035] In the sintered body of this embodiment, the amounts of [Fe2O3+Mn2O3+(3 / 2)ZrO2] and Fe2O3 are set within predetermined ranges, and the molar parts f, g and h of Al, Co and Cr are strictly controlled within the following ranges. 0.0012≦f≦0.010 (3) 0.0005≦g≦0.0015 (4) 0.0005≦h≦0.004 (5)
[0036] By limiting the contents of Al, Co, and Cr within the above-mentioned predetermined ranges, Cu segregation can be suppressed as shown in FIG. 1 of the examples described later, and high μ' can be realized in the high frequency range. The reason why Cu segregation can be suppressed by strictly controlling the contents of Al, Co, and Cr is considered to be as follows. Since Al, Co, and Cr are elements that are difficult to dissolve in spinel, it is presumed that when they are contained in excess, they combine with Cu, which is a liquid phase component, and form precipitates as impurities, causing Cu segregation. By suppressing the amounts f, g, and h of Al, Co, and Cr to 0.010 or less, 0.0015 or less, and 0.004 or less, respectively, Cu segregation can be suppressed and high μ' can be realized in the high frequency range. Al(f) is preferably 0.005 or less, more preferably 0.003 or less. Co(g) is preferably 0.0010 or less, more preferably 0.0008 or less. Cr(h) is preferably 0.0030 or less, more preferably 0.0015 or less. Cu segregation is likely to be formed in the range of [Fe2O3+Mn2O3+(3 / 2)ZrO2] of the sintered body of the present invention, i.e., in the case of a relatively high value of [Fe2O3+Mn2O3+(3 / 2)ZrO2], it is particularly important to strictly control the contents of Al, Co, and Cr. On the other hand, if the contents of Al, Co, and Cr in the sintered body are too small, it is difficult to form a liquid phase component, and the sinterability decreases, so it is presumed that μ' in the high frequency range decreases. Therefore, Al(f) is set to 0.0012 or more, and Co(g) and Cr(h) are set to 0.0005 or more. Al(f) is preferably 0.0015 or more, more preferably 0.0020 or more. Co(g) is preferably 0.0006 or more, more preferably 0.0007 or more. Cr(h) is preferably 0.0007 or more, more preferably 0.0010 or more.
[0037] According to the present invention, the amounts of [Fe2O3+Mn2O3+(3 / 2)ZrO2] and Fe2O3 are within prescribed ranges, and the amounts of Al, Co and Cr are strictly controlled within extremely small ranges, which was not possible in the prior art, thereby making it possible to more reliably improve μ' in the high frequency range.
[0038] The sintered body of this embodiment contains Fe, Ni, Cu, Zn, Zr, Mn, Al, Co, and Cr, for example, as a composite oxide. The sintered body of this embodiment may be a composite oxide of Fe, Ni, Cu, Zn, Zr, Mn, Al, Co, and Cr. The sintered body of this embodiment may contain inevitable impurities as described above.
[0039] In the sintered body of the present embodiment, it is further preferable that the d representing the Zr amount satisfies the following formula (6), and the e representing the Mn amount satisfies the following formula (7). 0.10≦d≦0.50 (6) 0.055≦e≦0.25 (7)
[0040] By setting the Mn content (e) within a predetermined range and adding ZrO2 so that the Zr content (d) is within the above range, μ' in the high frequency range can be further improved. This is thought to be because, by setting the Mn content (e) within a predetermined range and adding a predetermined amount of Zr, the magnetic anisotropy is reduced and μ' in the high frequency range is further improved. From the viewpoint of further reducing the magnetic anisotropy and further improving μ' in the high frequency range, the Mn content (e) is more preferably 0.064 or more and more preferably 0.22 or less. Moreover, the Zr content (d) is more preferably 0.20 or more and more preferably 0.40 or less.
[0041] In the sintered body of this embodiment, the ratio of (Ni+Cu) / Zn expressed by the molar concentration ratio corresponds to the Curie temperature, and the Curie temperature increases by increasing this ratio, although this is not particularly limited. Possible ranges for (Ni+Cu) / Zn include a range of 0.5 or more and 1.1 or less.
[0042] This embodiment is characterized by the component composition of the sintered body, and the manufacturing method thereof is not limited. As the manufacturing method, a conventional method can be adopted. For example, a method of mixing a plurality of oxides as a mixed raw material, adding pure water, and mixing additives such as a dispersant and a stabilizer can be mentioned. Instead of the oxides, or together with the oxides, compounds that form oxides by firing, such as halides and organometallic compounds, may be mixed.
[0043] The above blended raw materials are mixed to obtain a raw material mixture. For example, as in the examples described below, mixing and grinding can be performed using a ball mill. Next, the raw material mixture is calcined, for example, at 650°C or higher and 850°C or lower. After calcination, grinding is performed to obtain a pulverized material. At this time, a binder, sintering aid, etc. for molding and sintering can be added and mixed and ground. The mixed and ground material is granulated to obtain a granulated material, and then the granulated material is molded to obtain a molded body. Then, the molded body is fired, for example, at a temperature in the range of 900°C or higher and 1200°C or lower to obtain a sintered body. EXAMPLES
[0044] The present invention will be described in more detail below with reference to examples. The present invention is not limited to the following examples, and can be practiced with appropriate modifications within the scope of the above and below-mentioned aims, and all such modifications are included in the technical scope of the present invention.
[0045] [Preparation of ferrite sintered body] [Example 1] First, Fe2O3, CuO, NiO, ZnO, Mn2O3, ZrO2, Al2O3, Co3O4, and Cr2O3 were weighed as blended raw materials so that the compositions after firing would be those of Examples 1-1 to 1-9 in Table 1. In this example, in order to strictly control the contents of trace amounts of Al, Co, and Cr, oxide materials with high purity were prepared. The purity of the oxide materials was Fe2O3: 99.9%, ZnO: 99.7%, NiO: 99.3%, and CuO: 99.96%. Note that the amounts of the other oxide materials used were small, so the influence of impurities mixed in is considered to be extremely small.
[0046] The weighed raw materials were placed in a ball mill together with pure water, a dispersant, and PSZ (partially stabilized zirconia) balls, and wet-mixed and ground for 6 hours. After evaporating and drying, the mixture was calcined at 750°C for 2 hours to produce a calcined product (calcined powder).
[0047] The calcined powder obtained was placed in a ball mill together with pure water, a binder (acrylic binder), an antifoaming agent, and PSZ balls, and mixed and ground in a wet manner. The mixed and ground slurry was evaporated and dried, and then granulated to obtain a granular powder. The granular powder thus produced was filled into a mold with an inner diameter of 12 mm and an outer diameter of 20 mm, and pressure-molded to obtain a toroidal-shaped molded body. The molded body was then sintered in a sintering furnace at the sintering temperature shown in Table 1 for 1 hour in an air atmosphere, to obtain a toroidal-shaped ferrite sintered body.
[0048] [Example 2] Sintered bodies were produced in the same manner as in Example 1, except that Fe2O3, CuO, NiO, ZnO, Mn2O3, ZrO2, Al2O3, Co3O4, and Cr2O3 were weighed as the raw materials so that the composition after sintering would be the composition of Examples 2-1 to 2-7 in Table 1.
[0049] [Example 3] Sintered bodies were produced in the same manner as in Example 1, except that Fe2O3, CuO, NiO, ZnO, Mn2O3, ZrO2, Al2O3, Co3O4, and Cr2O3 were weighed as the raw materials so that the compositions after sintering would be the compositions of Examples 3-1 to 3-5 in Table 1.
[0050] [Comparative Example] Sintered bodies were prepared in the same manner as in Example 1, except that Fe2O3, CuO, NiO, ZnO, Mn2O3, ZrO2, Al2O3, Co3O4, and Cr2O3 were weighed as the raw materials so that the composition after sintering would be the composition of Comparative Examples 1-1 to 1-12 in Table 1.
[0051] [Evaluation of ferrite sintered body] Using the ferrite sintered bodies obtained in the above [Example 1], [Example 2], [Example 3] and [Comparative Example], the μ′ at 100 kHz and the Curie temperature were obtained as follows. Furthermore, the ferrite sintered bodies were observed with a microscope to confirm the presence or absence of Cu segregation, and the component composition was analyzed.
[0052] (Measurement of μ' and Curie temperature at 100kHz) The μ′ of the obtained sintered body was measured at 100 kHz using an impedance analyzer (Model 4294A, manufactured by KEYSIGHT TECHNOLOGIES). The obtained μ′ at 100 kHz is shown in Table 1.
[0053] In addition, the sintered compact was wound with Cu wire 20 times, and the temperature characteristics of μ' at 100 kHz were measured using an LCR meter (model E4980, manufactured by Agilent) to calculate the Curie temperature. The Curie temperature was calculated as follows. In a graph with temperature on the horizontal axis and μ' at 100 kHz on the vertical axis, the Curie temperature was determined as the temperature at which the line passing through the points where μ' is 80% and 20% when μ' at room temperature is 100%. When measuring the temperature, the sintered compact was placed in a thermostatic chamber (model STH-120, manufactured by ESPEC) and the temperature was changed from room temperature to 200°C. The calculated Curie temperatures (Tc) are shown in Table 1.
[0054] (Microscopic Observation) The toroidal ferrite sintered bodies of each of Example 1-1 and Comparative Example 1-3 were cut so that a cross section that was nearly perpendicular to the circumferential direction and nearly horizontal in the axial and radial directions could be observed, and the sintered bodies were embedded in resin using epoxy resin and a hardener. The cut surface of the sintered body embedded in resin was mirror-polished by an automatic polishing machine. SEM-WDX analysis was performed on the mirror-polished surface using a scanning electron microscope (JXA-8530F, manufactured by JEOL Ltd.) to obtain a backscattered electron image and determine the distribution state of Cu. The results are shown in FIG. 1. In FIG. 1, it can be seen that Cu segregation, shown as white dots, is observed more in the comparative example than in the examples. It is presumed that the Cu segregation in this comparative example occurs because the contents of Al, Co, and Cr are outside the specified range, as described above.
[0055] (Analysis of component composition and calculation of index α and β values) The obtained sintered body was pulverized in a mortar, and the contents of Fe, Zn, Ni, Cu, Zr, Mn, Al, Co, and Cr were measured using ICP-AES / MS. The molar parts of these elements contained relative to 100 molar parts of Fe were calculated and the results are shown in Table 1. In addition, when the molar parts of Zn, Ni, Cu, Zr, and Mn relative to 100 moles of Fe are a, b, c, d, and e, respectively, the α value (=100-ab-c+2d+(1 / 2)e) and β value (=a+b+c+d+e / 2) were calculated. In addition, (Ni+Cu) / Zn, which is closely related to the Curie temperature, was also calculated. These results are shown in Table 1.
[0056] [Table 1]
[0057] [Table 2]
[0058] Examples 1-1 to 1-9 in [Example 1], Examples 2-1 to 2-7 in [Example 2], and Comparative Examples 1-1 to 1-12 are examples in which the (Ni+Cu) / Zn ratio was controlled so that the Curie temperature was approximately 140. Based on these examples, the effect of the component composition on μ' at 100 kHz in this Curie temperature range was confirmed.
[0059] A comparison of Example 1-1 with Comparative Examples 1-1 and 1-2 shows that μ' in the high frequency range decreases when the Al content (f) is outside the upper and lower limits. Furthermore, a comparison of Example 1-1 with Comparative Examples 1-3 to 1-5 shows that μ' in the high frequency range also decreases when the Co content (g) and Cr content (h) are outside the upper and lower limits. These comparisons show that μ' in the high frequency range can be reliably improved by strictly controlling the contents of Al, Co, and Cr within an appropriate range of very small amounts.
[0060] Examples 1-2 to 1-4 are examples in which the α value was changed. Comparing Examples 1-2 to 1-4 with Comparative Example 1-6, it can be seen that when the α value falls outside the upper limit and the β value falls outside the lower limit, μ′ in the high frequency range decreases.
[0061] Example 1-5 and Examples 2-1 to 2-4 are examples in which the Zr amount (d) was changed. Comparative Examples 1-7 to 1-10 are also examples in which the Zr amount (d) was changed, and the α value was outside the range of the present invention. From a comparison between these Examples 1-5 and Examples 2-1 to 2-4 and Comparative Examples 1-7 to 1-10, it was found that the increase in the Zr amount (d) increased μ' in the high frequency region, but if the Zr amount was increased too much, the increase in μ' in the high frequency region was saturated. Also, even if the Zr amount (d) was increased, if the α value was outside the lower limit, μ' in the high frequency region decreased. In particular, from a comparison between Comparative Examples 1-7 to 1-9 and Comparative Example 1-10, if both the Zr amount (d) and the upper limit of the β value were exceeded, μ' in the high frequency region decreased considerably.
[0062] Comparing Example 2-1 with Example 1-9, it is clear that by setting the Mn content within the preferred range, μ′ is increased in the high frequency range.
[0063] Examples 1-6 to 1-8 are examples in which the Mn content (e) is relatively high. When Mn exceeds the preferred range, the effect of increasing μ' in the high frequency range by adding Zr is weakened. Comparing Examples 1-5 and 2-1 to 2-4 with Examples 1-6 to 1-8, when the Zr content is lower than 0.34, the examples with higher Mn content have higher μ' in the high frequency range, but when the Zr content is 0.34, the examples with lower Mn content have higher μ' in the high frequency range.
[0064] Examples 2-5 to 2-7 are examples in which the α value and the Zr content (d) were changed. Comparing Examples 2-5 to 2-7 with Comparative Example 1-11, it can be seen that as the α value and Zr increase, μ' in the high frequency range improves, but as the α value deviates from the upper limit, μ' in the high frequency range decreases. Comparing Comparative Example 1-11 and Comparative Example 1-12, in which the α value is out of range, it can be seen that as the α value and the Zr content (d) deviate from the upper limit, μ' in the high frequency range further decreases.
[0065] From the above examples, it can be seen that by setting the α and β values, i.e., [Fe2O3+Mn2O3+(3 / 2)ZrO2] and the amount of Fe2O3 within the specified ranges, it is possible to suppress the decrease in μ' in the high frequency region due to relaxation loss, and furthermore, by setting the Al amount, Co amount, and Cr amount within specified ranges, it is possible to suppress Cu segregation. As a result, a high μ' of more than 1600 can be achieved in the high frequency region at around Tc = 140°C.
[0066] Furthermore, as shown in [Example 2], by setting the Zr content and Mn content within a predetermined range, the magnetic anisotropy was reduced, and a higher μ' of 1700 or more could be achieved in the high frequency region at around Tc=140°C.
[0067] Furthermore, Examples 3-1 to 3-5 of [Example 3] are examples in which Tc was changed by changing (Ni+Cu) / Zn. Although Tc and μ' are in a trade-off relationship, in these examples, high μ' was obtained in the high frequency region at each Tc.
[0068] This application claims priority from Japanese Patent Application No. 2021-176701, which is incorporated herein by reference. [Industrial Applicability]
[0069] The sintered body of the present invention can be used as a sintered magnetic part in various electromagnetic apparatus / devices, such as inductors, transformers, coils, etc.
Claims
1. The present invention includes a spinel-type ferrite oxide having metal elements mainly composed of Fe, Ni, Cu, and Zn, Further comprising Zr, Mn, Al, Co and Cr; A sintered body in which, when Fe is 100 molar parts, the molar parts of Zn, Ni, Cu, Zr, Mn, Al, Co, and Cr are a, b, c, d, e, f, g, and h, respectively, satisfy the following formulas (1) to (5), where a is in the range of 23.9 or more and 34.6 or less, b is in the range of 6.7 or more and 27.0 or less, and c is in the range of 0.1 or more and 10.2 or less. 49.0<100-a-b-c+2d+(1 / 2)e<50.0...(1) 50.2<a+b+c+d+e / 2<52.7...(2) 0.0012≦f≦0.010 ... (3) 0.0005≦g≦0.0015 ... (4) 0.0005≦h≦0.004 ... (5)
2. The sintered body described in claim 1, wherein a is in the range of 30.0 or more and 33.6 or less, b is in the range of 12.5 or more and 17.1 or less, and c is in the range of 4.05 or more and 7.16 or less.
3. The sintered body according to claim 1 or 2, wherein d satisfies the following formula (6) and e satisfies the following formula (7). 0.10≦d≦0.50 ... (6) 0.055≦e≦0.25 ... (7)
Citation Information
Patent Citations
Production of manganese-zinc-based ferrite
JP1996259316A
Low-loss ferrite material and ferrite core using the same
JP2001176717A
Ferrite composition, ferrite core, and electronic component
JP2012096961A
Ferrite composition and electronic component
JP2016196397A
FERRITE POWDER AND MnZn FERRITE AND METHOD FOR PRODUCING THE SAME
JP2019073434A